Building a sustainable job-rich recovery (Geneva, 2011)
"The European Commission and the International Labour Organization have combined efforts in reaction to the deep crisis that hit the global economy in 2008. The aim of this joint project is to examine policies that will lead not only to a quicker recovery but also to a more sustainable, environmentally friendly and equitable global economy. This is particularly relevant given the uneven and fragile nature of the recovery process across and within countries. These efforts have culminated in the publication of two Synthesis Reports. The first report examines the origins of the crisis and provides an overview of immediate policy responses across both developed and developing economies; the second discusses green policies and labour market issues related to this necessary long-term economic transformation. Both reports are based on a series of technical discussion papers. This first report examines the origins of the deep financial and economic crisis that hit the world economy in 2008 and that continues to shape labour market performance across the globe. The report discusses general lessons to be learned form financial crises as well as the role of global imbalances that have taken a prominent place in the current crisis. The report then presents global stimulus measures and assesses their effectiveness, comparing them with earlier examples in Argentina and the Republic of Korea. Finally, the report provides an overview of policy measures to maintain the recovery momentum in times of increasingly reduced policy space, focusing on the importance of quality job creation and demand-led initiatives to build a sustainable job-rich recovery. "